Програмно-інформаційний комплекс моделювання систем теплопостачання - Denysov , Viktor (General Energy Institute of the National Academy of Sciences of Ukraine, 2022)
Software and information complex for modeling of the heat supply systems functioning, which allows ensuring the optimal selection of aggregates and their operation modes. It will ensure the production and redistribution of energy in accordance with the schedule of consumers. Simulation of optimized operating modes of a self-sufficient heat supply system for a cottage village based on local energy resources and with minimal use of external energy sources was performed. The use of the software and information complex made it possible to calculate the parameters that provide optimized coverage of the heat load schedule of the cottage village based on local energy resources. The simulation performed using the example of the predicted values of the installed thermal capacity of the power units and the actual ambient temperature schedule. The developed new software and information complex provides an opportunity for hourly simulation and research of optimal modes of operation of heat units of autonomous heat supply systems. In the developed software and information complex, a model of optimization of operating modes is applied, which belongs to the class of problems of optimal loading of generating capacities of power systems with the criterion of minimizing costs for production, accumulation and consumption of heat and electricity. An example of simulation results using the heat load schedule for the selected day of March 20, 2018 is given. The obtained results indicate a decrease in the specific cost of hourly heat supply with an increase in the part of thermal energy supplied at the expense of renewable energy sources, and accordingly, a decrease in the part of gas, and in the general case of any other generation based on fossil fuel technologies, in the total volume of heat supply. Thus, the effectiveness of the use of renewable energy sources based on local energy resources as part of the heat supply system of the cottage village confirmed.